Stabilitas Membran Sel Eritrosit Ekstrak, Fraksi Kloroform, Etil Asetat dan Metanol Herba Patah Tulang (Euphorbia Tirucalli L.) - Fika, Irma; Wirasti, Wirasti; Pambudi, Dwi Bagus; Waznah, Urmatul (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
Euphorbia tirucalli L. (patah tulang) contains secondary metabolites with potential anti-inflammatory activity. This study aimed to identify its bioactive compounds and evaluate erythrocyte membrane stabilization of the extract and fractions. Extraction was performed by maceration with 96% ethanol, followed by fractionation using chloroform, ethyl acetate, and methanol. Total flavonoid and phenolic contents were measured by UV-Vis spectrophotometry, while erythrocyte membrane stabilization was tested in vitro. Phytochemical screening revealed flavonoids, phenols, saponins, steroids, triterpenoids, and tannins. The phenolic content was 432.1 ± 99.4 mg/g in the extract, 1,057 ± 88.02 mg/g in the chloroform fraction, 254.4 ± 48.84 mg/g in the ethyl acetate fraction, and 643.2 ± 267.3 mg/g in the methanol fraction. The highest flavonoid content was found in the chloroform fraction (4.26 ± 0.12 mg/g), followed by the extract (3.63 ± 0.35 mg/g), ethyl acetate (3.56 ± 0.36 mg/g), and methanol (2.6 ± 0.03 mg/g). Membrane stabilization assays showed the extract provided the strongest protection (95.04%), followed by chloroform (89.51%), ethyl acetate (87.71%), and methanol (87.52%), approaching the positive control diclofenac sodium (90.59%). Kruskal-Wallis and Tukey tests indicated the ethanol extract at 100 μg/mL (p=0.997 >0.001) and chloroform fraction at 500 μg/mL (p=0.023 >0.001) were not significantly different from the control, while ethyl acetate and methanol fractions differed significantly (p<0.001). These results demonstrate that the ethanol extract and chloroform fraction possess the highest anti-inflammatory potential, supported by high phenolic and flavonoid levels and consistent statistical analysis.